Effect of Work Achievement, Incentives, Discipline and Leadership Style on Employee Performance - Ratnasari, Sri Langgeng; Kirin, Arwansyah; Susanti, Ervin Nora; Lestari, Linayati; Tanjung, Rona; Sutjahjo, Gandhi (Journal of Social Transformation and Regional Development, 2021)
The purpose of this study was to analyze the effect of work performance on employee performance, to analyze the effect of incentives on employee performance, to analyze the effect of discipline on employee performance, to analyze the influence of leadership style on employee performance, and to analyze the effect of work performance, incentives, discipline, leadership style. on employee performance. The population of this study were employees of PT. Austin Engineering Indonesia, amounting to 175 people in the store. The sample consisted of 175 respondents, who were taken with a saturated sampling method. Data analysis using multiple regression with SPSS. The results of this study can be concluded that work performance has a significant effect on employee performance, incentives have a significant effect on employee performance, discipline has a significant effect on employee performance, leadership style has a significant effect on employee performance. Job performance, incentives, discipline, and leadership style have a significant effect on employee performance.